ONE WORLD, MANY RELIGIONS: THE LOCAL WISDOM VALUE AND SOCIAL RELIGIOUS ORGANIZATIONS IN STRENGTHENING TOLERANCE - Nasriandi Nasriandi; Hadi Pajarianto; Makmur Makmur (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
The index of tolerance for harmony among religious communities in Indonesia is fluctuates, tends to strengthen but is still affected by intolerance cases which should not have happened at the first place. This study aims to identify the local wisdom value in maintaining diversity, and the role of socio-religious institutions to strengthen diversity. Qualitative research methods involve 30 informants selected by using purposive sampling and data collected within-depth interviews, in January-February 2023. data were analyzed thematically and carried out through three stages; data reduction, data display, and drawing conclusions and verification. The results of the research show that there is an implementation of the contact theory by utilizing local wisdom in the ethnic groups that inhabit this research locus are Sipakatau, Sigunakannge, and Sipakalebbi, Teposliro, Meyama-Braya, Asah, Asih, Asuh, and Banjar traditions. The implementation of these values is strengthened by socio-religious institutions consisting of religious and traditional leaders, youth, educational institutions, politicians, the economy, which also strengthen community contact activities, which functionally play a role in accordance with their respective fields. The contribution of this research is practically to strengthen tolerance in a diverse society, which is often affected by intolerance cases. The declaration of Kampung Pancasila at the research locus is a concrete manifestation of the will of the entire community to live together in a peaceful atmosphere.